Attempts to identify the molecular cause of autoinflammatory recurrent fever - Oksana Boyarchuk; Diana Savkiv (Rheumatology)
Systemic autoinflammatory diseases caused by dysregulation of the innate immunity are a known cause of recurrent fevers. We present the molecular diagnosis results of 12 children with recurrent fever, analyzing the correlation between molecular findings and clinical symptoms. No pathogenic variants confirming autoinflammatory disease were found. One child was diagnosed with SRP54 deficiency, linked to congenital neutropenia with a cyclic pattern. Variants of uncertain significance were found in 6 patients in genes associated with autoinflammatory disorders, though two lacked clinical correlation. Variants of uncertain significance in the NLRC4 gene were detected in 2 patients with periodic fever, aphthous stomatitis, pharyngitis, adenitis (PFAPA) syndrome, in the PLSG2 gene in 1 child with systemic juvenile idiopathic arthritis, and in the MEFV gene in 1 patient with syndrome of uncertain recurrent fever. COVID-19 was identified as a triggering factor in 54.5% of cases. Further research is needed to clarify the role of genetic variants and environmental factors in recurrent fevers.